?STUDY OF THE COUMARIN ANDVOLATILE OIL COMPOSITION FROM AERIAL PARTS OFACHILLEA MILLEFOLIUM L. (Biological Sciences - PJSIR, 2001)
Aerial parts of Achillea millefolium. L. (Farn. Asteraceae) were exhaustively extracted with ethanol (90%) and then the extract was fractionated into coumarin and unsaponifiable fractions. The coumarin fraction led to the isolation of scopoletin I, umbelliferone II and aesculetin III, whereas b-arnyrin, a mixture of steroidal components were identified using GLC. Besides, the volatile oils from the leaves and stems of A.millefolium were separately analyzed using GCIMS chromatographic analysis.